2011
DOI: 10.1016/j.jastp.2010.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Long-term solar activity influences on South American rivers

Abstract: River streamflows are excellent climatic indicators since they integrate precipitation over large areas. Here we follow up on our previous study of the influence of solar activity on the flow of the Parana River, in South America. We find that the unusual minimum of solar activity in recent years have a correlation on very low levels in the Parana's flow, and we report historical evidence of low water levels during the Little Ice Age. We also study data for the streamflow of three other rivers (Colorado, San J… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
2
24
0
1
Order By: Relevance
“…Moreover, the occurrence years of both the maximum number of sunspots and the maximum lunar declination angle basically correspond to the crests of the reconstructed runoff time series with fluctuation periods of 8.5-12 and 17-21.5 years (Figures 6a-6f). This finding indicates that the crests and troughs of SLPMs activity could diminish or enhance the runoff, which is in agreement with previous studies related to the stream flow of South American rivers (Mauas et al, 2008;Mauas et al, 2011). This finding indicates that the crests and troughs of SLPMs activity could diminish or enhance the runoff, which is in agreement with previous studies related to the stream flow of South American rivers (Mauas et al, 2008;Mauas et al, 2011).…”
Section: The Impacts Of Slpms On Extreme Hydrological Eventssupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the occurrence years of both the maximum number of sunspots and the maximum lunar declination angle basically correspond to the crests of the reconstructed runoff time series with fluctuation periods of 8.5-12 and 17-21.5 years (Figures 6a-6f). This finding indicates that the crests and troughs of SLPMs activity could diminish or enhance the runoff, which is in agreement with previous studies related to the stream flow of South American rivers (Mauas et al, 2008;Mauas et al, 2011). This finding indicates that the crests and troughs of SLPMs activity could diminish or enhance the runoff, which is in agreement with previous studies related to the stream flow of South American rivers (Mauas et al, 2008;Mauas et al, 2011).…”
Section: The Impacts Of Slpms On Extreme Hydrological Eventssupporting
confidence: 92%
“…The runoff of most rivers in the world has approximately quasi 2 years, 4-to 7-year, 8-to 12-year, and 17-to 21-year periods of frequency fluctuation, which could be affected by a very complex set of natural climatic variabilities (Agnihotri et al, 2002;Mauas et al, 2011). Internal climate variability or natural forcing (e.g., the Pacific Decadal Oscillation and the Atlantic Multidecadal Oscillation) is likely to be the direct driver of inducing oscillation of the rivers discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another distinct SSN–PAR connection is through the ∼30‐year oscillation, previously detected by Mauas et al () and Mauas et al () as a multidecadal oscillation. It seems to be significant in the Morlet WTC s/n local spectrum throughout the analysed period.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Mauas et al (), after the elimination of secular trends and cycles with periods equal or smaller than 11 years in the time series of the sunspot numbers (SSNs) and the Paraná River (PAR) discharges at Corrientes gauging station (Figure ), obtained strong positive correlations at interdecadal scales. Furthermore, Mauas et al () have shown similar results for San Juan, Atuel and Colorado subtropical Andean rivers. The authors propose that at multidecadal scales ‘ higher solar activity corresponds to larger precipitation, both in summer and in wintertime, not only in the large basin of the Paraná, but also in the Andean region north of the limit with Patagonia ’.…”
Section: Introductionmentioning
confidence: 99%